2015
DOI: 10.1016/j.cmi.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination during the first 6 months after solid organ transplantation is efficacious and safe

Abstract: Preventing influenza infection early after transplantation is essential, given the disease's high mortality. A multicentre prospective cohort study in adult solid organ transplant recipients (SOTR) receiving the influenza vaccine during four consecutive influenza seasons (2009-2013) was performed to assess the immunogenicity and safety of influenza vaccination in SOTR before and 6 months after transplantation. A total of 798 SOTR, 130 of them vaccinated within 6 months of transplantation and 668 of them vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
(49 reference statements)
3
20
0
4
Order By: Relevance
“…Different strategies can be used to increase vaccination efficacy such as the use of an adjuvanted vaccine that has been demonstrated to be safe inducing a protective immune response in SOTR ( 11 , 12 ). Our group demonstrated that having detectable antibody titers at vaccination improves the response to vaccination in SOTR supporting the administration of a booster dose of the influenza vaccine ( 13 , 14 ), that was later demonstrated to be safe and effective inducing an increased antibody response in a clinical trial ( 15 ).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Different strategies can be used to increase vaccination efficacy such as the use of an adjuvanted vaccine that has been demonstrated to be safe inducing a protective immune response in SOTR ( 11 , 12 ). Our group demonstrated that having detectable antibody titers at vaccination improves the response to vaccination in SOTR supporting the administration of a booster dose of the influenza vaccine ( 13 , 14 ), that was later demonstrated to be safe and effective inducing an increased antibody response in a clinical trial ( 15 ).…”
Section: Introductionmentioning
confidence: 83%
“…A recent study has shown no cross-reactivity between HLA class I and II and several virus-specific human monoclonal antibodies, suggesting that the emergence of anti-HLA antibodies in the setting of viral infections or vaccination may be due to bystander activation or dormant HLA specific B cells ( 28 ). Our group has demonstrated that administering the influenza vaccine 1 month post-transplantation is safe and efficacious ( 14 ), reporting no episodes of rejection, however, we did not address the de novo synthesis of DSA.…”
Section: Introductionmentioning
confidence: 99%
“…Eine Ausnahme stellt die saisonale Influenzaimpfung dar, deren Gabe bereits einen Monat nach NTx erfolgen kann. Die Impfung ist auch in den ersten 6 Monaten nach NTx sicher und effizient sowie vergleichbar mit der Gabe nach 6 Monaten [28]. Die Serokonversionsrate ist mit 15-90 % niedriger als in der Allgemeinbevölkerung.…”
Section: Prophylaxe Und Prävention Unter Immunsuppressionunclassified
“…61,62 However, a more recent prospective cohort study on 798 SOT recipients who were vaccinated before and after six months (130 vs. 668 respectively) after kidney, heart, and liver transplantation showed similar seroprotective immune response and safety profiles in both groups. 63 Therefore, it may be reasonable to administer influenza vaccine as soon as one month after transplantation.…”
Section: Timing Of Vaccinationmentioning
confidence: 99%